The inert Zee model (2016)
ABSTRACT: We study a realization of the topology of the Zee model for the generation of neutrino masses at one-loop with a minimal set of vector-like fermions. After imposing an exact Z2 symmetry to avoid tree-level Higgs-mediated avor changing neutral currents, one dark matter candidate is obtained from the subjacent inert doublet model, but with the presence of new co-annihilating particles. We show that the model is consistent with the constraints coming from lepton avor violation processes, oblique parameters, dark matter and neutrino oscillation data.